Identification of cubebin and epicubebin isolated from Piper cubeba L.f fruits with two D-NMR spectroscopy - Wahyono .; S. Wahyuono; A. Mursyidi; H. Timmerman; R. Verpoorte; L. Hakim (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2005)
One of the isolated active compound of the tracheospasmolytic from kemukus fruits (Piper cubeba L.f) is cubebin. The problem occurred when cubebin (C20H20O6) mixed with its epimer because of the difficultly to identify the structure by 1D-NMR spectroscopy. Structure identification then was conducted by 2D-NMR spectroscopy, so the structure of cubebin and epicubebin can be clear identified. Key words : Cubebin, epicubebin, identification, 2D-NMR